BOVINE EMBRYO PRODUCTION BY IN VITRO FERTILIZATION USING CRYOPRESERVED GAMETES - Huyền, Nguyễn Thị Thương (Vietnam Journal of Biotechnology, 2011)
This research aimed at bovine embryo production, using cryopreserved mature bovine oocytes by vitrification, and cryopreserved sperms. The cumulus-oocyte complexes (COCs) were obtained from cow ovaries by aspiration. COCs with three or more layers of cumulus cells and homogeneous cjftoplasm were selected to be cultured in Ci medium (TCM-199, 10% FBS, 10 ng EGF, 0.2 mM Na pyruvate, 50 (ig/ml gentamicin) under the condition at 38.5°C with humidified atmosphere of 5% CO2 in au. After 22 - 24 h incubation, matured oocytes were cryopreserved by vitrification method in sfraws in two steps: (i) oocytes were first equilibrated in the VS, solution (TCM-199 + 10% FBS + 10% DMSO + 10% EG) for 45 seconds; (ii) The oocytes were then fransfenred in the VS2 solution (TCM-199 + 10% FBS -I- 20% DMSO + 20% EG + 1 M sucrose) for 25 seconds. Each sfraws were loaded with five to seven oocytes. Sfraws were plunged directly into hquid nifrogen within 25 - 40 seconds at the begirming of the exposure to second step. After storage in hquid nitrogen, thrawing was performed by exposing the sfraw to air for 5 seconds, and plunged into warm water (37°C) for 10 seconds, and then fransfered were oocytes into clean dish (<1>35); Oocytes were directly expelled into RD, medium (TCM-199 -1- 10% FBS -1- 0.25 M sucrose) 1.5 minutes, RD2 medium (TCM-199 -1-10% FBS + 0.15 M sucrose) 1.5 minutes and RD3 (TCM-199 + 10% FBS) medium 5 minutes; This oocytes were franferred to Cj medium and holding for 3 minutes. The thrawing was performed in a room at 25°C. After 22 - 24 h incubation, the number of oocytes observed with Metaphase 11 stage were 2658/3276 (81.19 ± 2.75%); morphological intact recovered rate was 76.08%. After 22 - 24 h incubation with sperm, insemination rate (two-cell embryo) was 11.67% and 46/144 embryos developed into blastocyst stage.